Bringing the power of information to life – the case of EMC Corporation - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Technology, markets and customer needs are changing. EMC Corporation, which started as a memory board maker thirty years ago, has been changing along. More well-known in the technology industry for its range of hardware used to store data, the company now positions itself as an “information storage vendor”, where software and services plays a greater role. Along with this repositioning, the company is actively managing what the EMC brand stands for, says EMC’s Steven Leonard.